Decadal changes in vegetation of a subarctic salt marsh used by lesser snow and Canada geese - Kotanen, Peter M.; Abraham, Kenneth F. (Plant Ecology, 2013)
This is the accepted manuscript of an article published by Springer Verlag. In the Hudson-James Bay system, grubbing and grazing by lesser snow geese have resulted in severe devegetation of coastal marshes. These changes likely represent an example of an alternative stable state; however, long-term datasets documenting whether revegetation is occurring are scarce. Here, we report results of a 10-year study investigating changes in the state of a degraded salt marsh system on the north coast of Akimiski Island, Nunavut. Four transects were intensively sampled in 1998 and 2008, two within the dense nesting and brood-rearing area of a snow geese colony, one on the colony edge, and one outside it; all of these sites were also used by broods of Canada geese. Key forage species (Puccinellia phryganodes, Festuca rubra, Carex subspathacea) were less common near the colony centre than elsewhere; biomass of Puccinellia also tended to be lower in more central areas. Forage species often increased in abundance between samplings, but the magnitude of changes was small. In contrast, non-forage species (Salicornia, Spergularia, Glaux) often reached high abundance within the colony centre; some (Salicornia) decreased while others (Spergularia) increased. We argue the degraded state was initiated by foraging damage from an exceptional stopover of 295,000 staging birds in 1972 and that the combined foraging pressure of relatively small numbers of nesting and migrant geese since then, coupled with soil changes, has been sufficient to maintain devegetated areas as a persistent alternative state. Whether or not this state is truly stable, further recovery is likely to be very slow. This is a contribution of the Wildlife Research and Development Section of the OMNR. This research was supported by NSERC (PMK), the Ontario Ministry of Natural Resources (KFA), the Arctic Goose Joint Venture (Hudson Bay Project), the Mississippi Flyway Council and the Central Flyway Council.